To Assess Vitamin D Levels in Patients Diagnosed as Fibromyalgia in Patients Attending Dow University Hospital (Medical Forum Monthly, 2024)
Objective: To assess the Vitamin D levels in patients diagnosed as fibromyalgia in patients attending Dow University Hospital Karachi.Study Design: Descriptive studyPlace and Duration of Study: This study was conducted at Dow University Hospital, Karachi from 21st January 2013 to 30th December 2013.Materials and Methods: 83 patients were selected from the outpatient department of medicine OPD. Results: among 83 patients who were enrolled in the study 60 (72.71%) were male and 23were (27.71) were females ages were between 7 and 70 years. the vitamin D levels ranged between 2 and 58with mean vitamin D level found to be 12,58 which is counted as moderate deficiency.Results: 83 patients with fibromyalgia were included in study. Among them who were enrolled in the study 60 (72.28%) were male and 23 (27.71%) were females .The subjects included in study age between 17 and 70 with mean age of 39.69 years. The fibromyalgia was gauged on clinical assessment. Vitamin D levels were classified. Vitamin D levels ranged between 2 and 58 with mean 12.58. As objective of study to assess vit D levels in diagnosed fibromyalgia patients in our population it was found that relationship between two parameters in significant.Conclusion: Vitamin D deficiency is frequently diagnosed in patients with fibromyalgia and nonspecific musculoskeletal pain in study population.